Mapping and modelling greenhouse gas emissions in CCAFS’ sites in South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Measurement of greenhouse gas emissions from agriculture activity requires expensive equipment and human resources to proceed on a continuous basis and to provide annual and seasonal emission estimates. Also, estimation of spatial-temporal distribution of agricultural emissions using ﬁeld data is time consuming and limited in its scope. Process-based bio-geochemical models, coupled with spatial data on soil properties, crop distribution and rotation, climate and agricultural management can provide estimates of greenhouse gas emissions from agricultural landscapes.